The Institutional Design Of The Governance Of Waste Water Domoestik Case Study Of Regional Water Company Tirtaweing The City Of Bandung - Boy Tagajagawani (International Journal of Educational Research & Social Sciences, 2021)
The research aims to study about the design of the institutional governance of domestic waste water, case study of regional water company Tirtawening city Bandung. The approach of research used in this study is using a qualitative descriptive approach, the Technique of data collection is done through observation, interview, document study to gather information related to the management of domestic waste water in the regional water company Tirtawening city Bandung. The results of research on the institutional design of the governance of domestic waste water regional water company Tirtawening city Bandung current needs to be done strengthening institutional governance is better again, so that the strategy adopted is through the institutional arrangement in the form of restructuring the organization to pay attention to organizational culture, leadership and structure of a slender, flexible, responsive, and efficient.